FoodSTART+ Asia. Food resilience through root and tuber crops in upland and coastal communities of the Asia-Pacific region. Project profile. - International Potato Center (International Potato Center, 2019)
Roots and tubers have great potential to support food security and resilient livelihoods among the poorest and most vulnerable people around the globe. FoodSTART, which promotes innovations for enhanced production and marketing of these underexploited crops, has completed a second phase in Asia.